2005
DOI: 10.1177/0013164405278557
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Reliability of the Beck Anxiety Inventory Scores

Abstract: Anxiety is one of the most pervasive symptoms seen in clinical psychological disorders. The Beck Anxiety Inventory (BAI) is a popular measure to assess the construct of anxiety. This study was concerned with an examination of potential study factors that are associated with the variability of the reliability estimates of the BAI scores. A review of the literature involving the BAI showed that more than 57% of the publications either did not mention reliability estimates for BAI scores or presented secondary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 67 publications
4
44
2
1
Order By: Relevance
“…Test-retest coefficients have been collected for the several psychometric instruments. [79][80][81][82][83][84][85][86][87][88][89][90] …”
Section: Methodsmentioning
confidence: 99%
“…Test-retest coefficients have been collected for the several psychometric instruments. [79][80][81][82][83][84][85][86][87][88][89][90] …”
Section: Methodsmentioning
confidence: 99%
“…A review of the BAI's use in the literature showed alpha coefficients are generally reported at .83 or better. While test-retest coefficients are reported from .35 to .83, this variability is likely due to the wide range of time intervals used (between 1 and 16 weeks) in these studies, where the BAI is only designed to measure symptoms experienced in past week (de Ayala et al, 2005). Symptoms are rated on a four-point Likert scale (0 = Not At All, 1 = Mildly, 2 = Moderately, and 3 = Severely) and scores are derived from adding the values of all responses.…”
Section: Dula Dangerous Driving Index (3di)mentioning
confidence: 99%
“…Affective symptoms were assessed during a shorter time frame than symptoms of eating disorders. However, the depression and anxiety measures used in the present study exhibit moderate temporal stability among youth (de Ayala, Vonderharr-Carlson, & Kim, 2005;Roberts, Andrews, Lewinsohn, & Hops, 1990). Although the Eating Disorder Diagnostic Scale has not previously been validated in samples of men, the internal consistency of the measure and pattern of association with other variables was similar across gender.…”
Section: Discussionmentioning
confidence: 63%